Empathy and occupational burnout syndrome in regular basic education teachers in Lima Metropolitana - Romero Llanos, Katherine (2019)
The aim of this research is to determine the relationship between empathy and occupational burnout syndrome in teachers of regular basic education in Lima Metropolitan; with a sample of 249 teachers of the primary and high school levels. The type of research is quantitative descriptive basic of correlational scope. As measuring instruments, the Interpersonal Reactivity Index (IRI) and the Maslach-ES Burnout Inventory (MBI) were administered. The results showed that the measured variables presented statistically significant strong and very strong non-linear correlations, obtaining the highest correlation between Perspective Taking (cognitive empathy) and Personal Achievement (burnout); and the lowest between Fantasy (cognitive empathy) and Depersonalization (burnout). One of the suggestions made was that the educational institutions of the country disseminate knowledge about the negative consequences of professional burnout in personal, professional and organizational life and the importance of training and regulating the empathy that allows achieving a healthy socio-emotional development in teachers and students.